Supporting Scientific Advice through a Boundary Organization. Issue 9 (12th September 2018) - Kennedy, Eric B.
Abstract: The complex socio‐environmental issues faced by society – including climate change, resource management, and fostering resiliency in landscapes that intermix human and natural features – are difficult challenges that demand contextually appropriate evidence‐based interventions. Institutional arrangements for providing scientific advice range from individual science advisors to large scientific committees or advisory councils, with a great deal of variation in their formal and informal structures. Regardless of the structuring of advisors, however, these arrangements face a common challenge: being required to speak to a wide range of issues in a time‐sensitive manner, each of which has extensive stakeholder communities, deep disciplinary knowledge, and many complicating attributes. It is argued that creating a formally associated, supporting boundary organization that is tasked with supporting the advisory functions can help to resolve this challenge and improve the overall quality of advice offered. Using a case study – the California Ocean Science Trust and its advice on coastal and ocean management issues – it is argued that boundary organizations can help science advisors maintain links with disparate stakeholder communities, adjudicate between competing forms of expertise, help to provide nuance in grappling with the tensions between science and politics, and support an "honest broker" advising function. Abstract : The quality of scientific advice can be improved through creating supportive boundary organizations. Boundary organizations can help science advisors maintain links with disparate stakeholder communities, adjudicate between competing forms of expertise, help to provide nuance in grappling with the tensions between science and politics, and support an "honest broker" advising function.